Psychotherapy for complex post-traumatic stress disorder: efficacy and therapeutic factors - Katalan, Cenya; Unterrainer, Human-Friedrich; Gelo, Omar C. G. (Frontiers in Psychology, 2026)
The treatment of patients with complex post-traumatic stress disorder (CPTSD) presents significant challenges due to the complexity and severity of the condition. Individuals who have experienced prolonged trauma exhibit, alongside post-traumatic stress disorder symptoms, disturbances in self-organization (DSO). This state of affairs not only complicates the psychotherapeutic process but also impacts the outcomes, making the treatment challenging. This article provides a narrative review of treatment approaches for CPTSD [including dialectical behavior therapy (DBT), cognitive-behavioral therapy (CBT), trauma-focused therapy (TFT), eye movement desensitization and reprocessing (EMDR), and psychodynamic therapy], with a specific focus on their outcomes and therapeutic factors. Standard evidence-based therapies (e.g., CBT, EMDR, exposure-based treatments) have been shown to be effective in reducing the core symptoms of PTSD but with more variable and often smaller effects for DSO symptoms. Phase-based approaches, including those that integrate evidence-based methods, have shown more significant results in affect regulation, self-concept, and interpersonal functioning. Psychodynamic therapies have shown enduring improvements, especially in the areas of identity and interpersonal relationships. The therapeutic alliance, trust, rupture repair, and the therapist’s empathy emerged as key components for treatment efficacy, especially in fostering safety and emotional regulation. These variables enabled corrective relational experiences and maintained engagement in therapy. These findings highlight the need for personalized, phased interventions that combine evidence-based strategies with a strong relational focus, as found in psychodynamic approaches. Addressing both symptom relief and reduction in DSO requires constant attention to the therapeutic process. The quality of the therapeutic alliance and the therapist’s responsiveness are fundamental to supporting long-term recovery. The article provides insight into the current issues associated with each treatment approach and future directions.